2012
DOI: 10.1002/j.1681-4835.2012.tb00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Data Quality in the Banking Supervisory Data of Southern Africa Central Banks

Abstract: The importance of effective supervision of banking institutions in developing countries cannot be over-emphasised. Central banks are responsible for the supervision of the banking institutions of a country. In order to effectively perform the supervisory role of banking institutions, central banks need to collect and analyse data about the operations of the banking institutions they supervise. Data analysis is conducted in order to establish the health of these institutions. Central banks in the SADC region ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Examples include: A survey of challenges facing South African Chief Information Officers (K. Johnston, Muganda, & Theys, 2007), a survey of the impact of Black Economic Empowerment on IT Governance implementation (Mohapi & Njenga, 2012), and a survey of knowledge management practices among South African firms (Naicker & Omer, 2015). Other topics under the general business heading are trade (Bankole, Osei-Bryson, & Brown, 2015) and banking (Motjolopane & Lutu, 2011). The ICT4D concern of the business papers was not so much to promote socio-economic development, but rather to acknowledge the developing country context (A.…”
Section: General Businessmentioning
confidence: 99%
“…Examples include: A survey of challenges facing South African Chief Information Officers (K. Johnston, Muganda, & Theys, 2007), a survey of the impact of Black Economic Empowerment on IT Governance implementation (Mohapi & Njenga, 2012), and a survey of knowledge management practices among South African firms (Naicker & Omer, 2015). Other topics under the general business heading are trade (Bankole, Osei-Bryson, & Brown, 2015) and banking (Motjolopane & Lutu, 2011). The ICT4D concern of the business papers was not so much to promote socio-economic development, but rather to acknowledge the developing country context (A.…”
Section: General Businessmentioning
confidence: 99%
“…Similarly, Su et al (2009) discussed the illustration of a quantitative method that confirmed the poor DQ risks in decision support for a finance company. In their analysis, they proposed identifying the relevant DQ dimensions as one requirement to fully implement the information quality programmes in financial institutions (Motjolopane and Lutu, 2011).…”
Section: Dq For Financial Institutionsmentioning
confidence: 99%